WE1.10 Acute Diverticulitis: Are We Following National & International Guidance On Antimicrobial Strategy For Uncomplicated Cases?. (9th August 2022) - Patel, Nikheel; Oladeji, Emmanuel; Bains, Parisha; Day, Nigel; Gupta, Ashish
Abstract: Aims: Uncomplicated acute diverticulitis is conventionally treated with antibiotics. Emerging evidence has suggested a non-antimicrobial approach in systemically well patients is a safe alternative strategy. Our aim was to assess adherence to national (NICE) & international (WJES) guidelines for uncomplicated cases. Methodology: Data was gathered from PACS imaging & discharge summaries retrospectively (1st October 2020–1st March 2021).The inclusion criteria was: CT confirmed cases of modified Hinchey stage 0 or 1a. The cohort was stratified into systemically well or unwell based on: admission CRP <150, observation score <2 (NICE sepsis stratification), immunocompetance status & Charlson score <3, as evidenced in the literature. Results: There were 48 patients included (female 29 vs male 19). The number of systemically well patients was 32 (67%) & unwell 16 (33%). Compliance to guidance 1 (NICE) - 'systemically well & therefore no antibiotics', was low with only 2/32 (6%) patients. Of the remaining, 14/30 (47%) were given intravenous antibiotics. Compliance to guidance 2 (NICE) - 'systemically unwell & therefore oral antibiotics', was 4/16 (25%) with the remaining majority of 12/16 (75%) treated with intravenous form. The median number of inpatient nights was 1.48 (well: 1.28 vs unwell: 1.88). Conclusions: The majority of patients with uncomplicated diverticulitis were systemically well. Compliance with guidelines on antimicrobial strategy was low. The incorporation of a risk stratification tool as demonstrated, allows for identification of patients that be discharged (with ambulatory follow up) after assessment. CT scans should be reviewed by radiologists with a multidisciplinary discussion on the most appropriate antimicrobial strategy.